Male long-Evans rats: An outbred model of marked hypothalamic-pituitary-adrenal hyperactivity - Sanchís-Ollé, Maria (Neurobiol Stress, 2021)
Rat and mouse strains differ in behavioral and physiological characteristics, and such differences can contribute to explain discrepant results between laboratories and better select the most appropriate strain for a particular purpose. Differences in the activity of the hypothalamic-pituitary-adrenal (HPA) axis are particularly important given the pivotal role of this system in determining consequences of exposure to stressors. In this regard, Long-Evans (LE) rats are widely used in stress research, but there is no specific study aiming at thoroughly characterizing HPA activity in LE versus other extensively used strains. In a first experiment, LE showed higher resting ACTH and corticosterone levels only at certain points of the circadian rhythm, but much greater ACTH responsiveness to stressors (novel environment and forced swim) than Sprague-Dawley (SD) rats. Accordingly, enhanced corticotropin-releasing hormone (CRH) expression in the paraventricular nucleus of the hypothalamus and reduced expression of glucocorticoid receptors were observed in the hippocampal formation. Additionally, they are hyperactive in novel environments, and prone to adopt passive-like behavior when compared to SD rats. Supporting that altered HPA function has a marked physiological impact, we observed in another set of animals much lower thymus weight in LE than SD rats. Finally, to demonstrate that LE rats are likely to have higher HPA responsiveness to stressors than most strains, we studied resting and stress levels of HPA hormones in LE versus Wistar and Fischer rats, the latter considered an example of high HPA responsiveness. Again, LE showed higher resting and stress levels of ACTH than both Wistar and Fischer rats. As ACTH responsiveness to stressors in LE rats is stronger than that previously reported when comparing other rat strains and they are commercially available, they could be an appropriate model for studying the behavioral and physiological implications of a hyper-active HPA axis under normal and pathological conditions.